Analysis of Basic Testing Using Smoke Testing in Asset Inventory Information Systems - Anardani, Sri; Jayadi, Puguh; Harly, Daniswara Andhika Putra (Information Technology and Science (ITScience), 2024)
The creation or development of a system must go through a testing phase with the aim that before the system is implemented by the user, bugs or errors can be detected at the start. The PGRI Madiun University Asset Inventory and Documentation Unit (UIAD) is currently building and developing an information system for managing inventory, asset and document data. So far, data management still uses manual recording on paper forms. This creates a problem of inconsistency between data in the field and data in the unit. To improve the quality of the UIAD information system so that it is more optimal, it is necessary to carry out basic testing with smoke testing to ensure that the basic features function properly. The aim of this research is to test the basic functionalities of the UIAD information system with smoke testing to provide recommendations for improvements in order to improve the quality of the UIAD information system. Testing is carried out manually with 3 types of test cases, namely login test case, master test case and asset test case. The test results show that the login test case passed 100%, the master test case passed 100%, and the asset test case passed 80%. Based on the test results, it is very important to carry out smoke testing on the basic functions of the system before the system is used so that bugs or errors can be found so that corrective action can be taken more quickly.